STREPTOCOCCUS MUTANS AND LACTOBACILLI ON GLASS IONOMER CEMENTS - Gabriela, Beresescu; Monea, Adriana; Ormenisan, Alina; Mucenic, Simona (European Scientific Journal, ESJ, 2015)
The purpose of this study was to evaluate the quantity of Streptococcus mutans and lactobacilli on enamel surfaces and one year old glass ionomer cement and compomer. The class V fillings, with their cervical margins placed subgingivally, were placed in the incisor, canine and premolar. The teeth to be filled had cervical abrasion or erosion defects. The evaluation was done in a cross sectional study, where the patients continued to use their customary oral hygiene procedures and during a 14-day period of experimental plaque formation. In this study no difference was seen in the number of bacteria recovered from one year old glass ionomer cement fillings compared to the enamel and composite resin surfaces. The fluoride levels in plaque adjacent to glass ionomer cement did not become high enough to inhibit the accumulation of the investigated bacteria. In this study we found that there was the same critical levels of Streptococcus mutans on glass ionomer cement and compomer. Only one of the test subjects had a number of lactobacilli. Differences in numbers of bacteria on the teeth could be due to different toxicologic effects of the restorative materials. The levels reached in plaque adjacent to the material did not become high enough to inhibit the growth of Streptococcus mutans and lactobacilli.